Identification of Selective CYP3A7 and CYP3A4 Substrates and Inhibitors Using a High-Throughput Screening Platform - Kabir, Md; Padilha, Elias C.; Shah, Pranav; Huang, Ruili; Sakamuru, Srilatha; Gonzalez, Eric; Ye, Lin; Hu, Xin; Henderson, Mark J.; Xia, Menghang; Xu, Xin (Frontiers in Pharmacology, 2022)
Cytochrome P450 (CYP) 3A7 is one of the major xenobiotic metabolizing enzymes in human embryonic, fetal, and newborn liver. CYP3A7 expression has also been observed in a subset of the adult population, including pregnant women, as well as in various cancer patients. The characterization of CYP3A7 is not as extensive as other CYPs, and health authorities have yet to provide guidance towards DDI assessment. To identify potential CYP3A7-specific molecules, we used competitive inhibition (P450-Glo) CYP3A7 assay to screen a library of ~5000 compounds, including FDA-approved drugs and drug-like molecules, and compared these screening data with that from P450-Glo CYP3A4 assay. Additionally, a subset of 1000 randomly selected compounds were tested in a metabolic stability assay. By combining the data from the qHTS P450-Glo and metabolic stability assays, we identified several chemical features important for CYP3A7 selectivity. Halometasone was chosen for further evaluation as a potential CYP3A7-selective inhibitor using docking simulation. From the metabolic stability assay, we identified twenty-two CYP3A7-selective substrates over CYP3A4 in supersome setting. Our data shows that CYP3A7 has ligand promiscuity, much like CYP3A4. Furthermore, we have established a large, high-quality dataset that can be used in predictive modeling for future drug metabolism and interaction studies